Hearing Outcomes after Ossicular Reconstruction with Removal of the Malleus. (29th August 2017) - Haberman, Rex S.; Salapatas, Anna M.
Abstract : Objectives: (1) Evaluate hearing outcomes of patients after planned malleus removal during ossicular chain reconstruction. (2) Analyze hearing results for titanium (Ti) and hydroxyapatite (HA) total ossicular prostheses (TOPs) and partial ossicular prostheses (POPs). (3) Compare Ti and HA partial prostheses. Study Design: Retrospective case series with chart review. Setting: Tertiary health care organization. Subjects and Methods: A chart review was conducted of 139 consecutive patients who presented with chronic otitis media with perforation (with or without cholesteatoma) and were treated with initial‐stage tympanoplasty (with or without mastoidectomy) and managed with TOP (n = 22) or POP (n = 117) between July 2010 and July 2015. The malleus was completely removed in all cases. Hearing was assessed via bone and air conduction pretone averages (0.5, 1, 2 kHz) pre‐ and postoperatively. Air‐bone gap (ABG) and change in ABG (ΔABG) were analyzed. Pre‐ and postoperative values were compared. Results: The overall mean ABG decreased from 29.4 ± 12.3 dB to 18.2 ± 11.4 dB postoperatively ( P <. 001) with a mean ΔABG of 14.5 dB (95% CI, 12.793‐16.203). Overall success was achieved by 69.1%. The POP group achieved higher success (70.9%) than the TOP group (59.1%; P =. 0001). Mean ABG decreased significantly within surgical groups (TOP and POP) and prosthesis material groups (Ti and HA; all P <. 001). Ti had statistically higher success than HA in both techniques: POP ( P =. 0478) and TOP ( P =. 0251). There was a 98% graft take rate. Conclusion: Planned malleus removal during ossicular chain reconstruction, regardless of disease extent, allows for simpler reconstruction and comparable favorable results to preservation of the malleus and should be considered during surgical planning.